Anatomical Variations of the Sciatic Nerve Exit from the Pelvis and Its Relationship with the Piriformis Muscle: A Cadaveric Study - Juan Pablo Reynoso; Manuel De Jesus Encarnacion; Renat Nurmukhametov; Dmitry Melchenko; Ibrahim E. Efe; Evgeniy Goncharov; Angel Alfonso Taveras; Issael Jesus Ramirez Pena; Nicola Montemurro (MDPI AG, 2022)
Background: The sciatic nerve (SN) is the widest nerve of the human body that exits the pelvis through the greater sciatic foramen, usually below the piriformis muscle (PM), and descends between the greater trochanter of the femur and ischial tuberosity of the pelvis to the knee. The aim of this paper is to examine and identify the SN variations in relation to the PM, its prevalence, pattern, and course. Methods: A prospective-descriptive cross-sectional study was carried out to determine the frequency of anatomical variations in the exit of the SN in relation with the PM in 20 anatomical bodies (corpses) of both genders, in equal numbers. Results: The dissection of 40 SNs in corpses of both sexes in equal numbers showed that the SN exited inferior to the PM in 37 lower limbs (92.5%); between the fascicles of the PM and inferior to the PM in two lower limbs (5%); and in one thigh, between the fascicles of the PM and superior to the PM (2.5%). Our study reported that the SN divides in its terminal branches more commonly in the proximal part of the popliteal fossa in 55% of cases, in the gluteal region in 35% of cases, and in the middle third of the thigh in 10% of cases. Conclusions: Anatomical variations of the SN in relation to the PM are challenging for the diagnostic and therapeutic procedure in many clinical and surgical cases. Rapid recognition of the SN changes makes surgical approaches more accurate and effective. Our study confirmed that the SN exits the pelvis most commonly below the PM, although some anatomical variations may occur.